2006
DOI: 10.1248/bpb.29.2350
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Mercury in Transgenic Tobacco Expressing Bacterial Polyphosphate

Abstract: Mercury pollution is a worldwide problem in environments, resulting primarily from its industrial use in bleaching operations, as a catalyst, as a pigment in paints, and in the mining of gold. The effects of this heavy metal on the ecosystem and human health are growing concerns. Decontamination of mercury in the sediment and soil around industrial plants has been a challenge for a long time. Unfortunately, numerous sites contaminated with mercurials have not been remediated because of the high costs of dredgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…In agreement with our previous results, 9,10) the ppk-transgenic tobacco showed more resistance to Hg 2ϩ than its wild-type progenitors (Fig. 3).…”
Section: Expression Of Mert Gene In Ppk/mert-transgenicsupporting
confidence: 93%
See 4 more Smart Citations
“…In agreement with our previous results, 9,10) the ppk-transgenic tobacco showed more resistance to Hg 2ϩ than its wild-type progenitors (Fig. 3).…”
Section: Expression Of Mert Gene In Ppk/mert-transgenicsupporting
confidence: 93%
“…20) Previously, we reported that tobacco plants expressing polyP in the absence of MerT, accumulated 2-6-fold more mercury than its wild-type progenitors from soils containing Hg 2ϩ concentrations over a range of 2.5-10 mM, but did not accumulate appreciable amounts of Hg 2ϩ compared with the wild-type control from soils containing Hg 2ϩ concentrations below 1.25 mM, despite its possession of polyP. 9,10) These previous observations together with the fact that mercury accumulation was accelerated by expression of MerT in tobacco plants inspired us to ascertain the efficiency and potential of ppk/merT-transgenic tobacco for use in the phytoremediation of low levels of mercury contamination, which is generally believed to be difficult to cleanup using natural or genetically-engineered plants without transport systems for the pollutant. Tobacco engineered to express mercury transporter and polyP accumulates effectively Hg 2ϩ at a range of low concentrations of Hg 2ϩ (0.1-1.25 mM) (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations